“Halal” Abortion in Perspective Common Law system,Civil Law System and Ius Constituendum : Towards Legality and Safety - Sardjana Atmadja (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2020)
Background: To safe services in hygienic conditions must be made widely available and affordable, so that the stigma associated with providing and obtaining abortions can lessen and safe services can become normal and accepted, abortion is broadly legal, widely available and safe in Indonesia.Objective: The purpose of this article to discuss ius constituendum on abortion in Indonesia from criminal law perspective between Common Law System and Civil Law System.In Indonesia Ius Contituendum on abortion is not directed to legalization of abortion as carried out both in Netherland and USA but tends to be harmonized with therapeutic abortion concept both medical and psychiatric fields.Material and Method: Systematic review of studies evaluating the prevalence of unsafe abortion in Indonesia.Results: The public health tragedy caused by unsafe abortion is all the more so because it is largely preventable, by improving the quality and availability of post abortion care, by making abortion legal and increasing access to safe services, and—because almost every abortion is preceded by an unintended pregnancy—by expanding access to contraceptive information and services. Restrictive laws have much less impact on stopping women from ending an unwanted pregnancy than on forcing those who are determined to do so to seek out clandestine means. Ironically, the abortion laws governing of Indonesia is holdovers from the colonial era.Conclutions: “Halal” abortion is making a significant contribution toward reducing the need for abortion altogether and the likelihood of unsafe abortion by bringing down the rates of unintended pregnancy. This is also helping to reduce complications of unsafe abortion through its support for programs to increase access to and improve post abortion care. This includes not only treatment for septic or incomplete abortion, but also essential post abortion.Keywords: “Halal” abortion, the public health tragedy, unintended pregnancy Common law system,Civil law system and Ius Constituendum.